Music As A Medium Of Peace: A Sociological Analysis Of “Heal The World” In The Context Of Sustainable Development Goals (SDGs) - Mesya Natalia Siboro; T. Thyrhaya Zein; Suryani Praysiska Silalahi; Giana Natasha Darosi Br. Sitepu; Felix Christian Tampubolon; Qaisha Arbey Prawira (Kopula: Jurnal Bahasa, Sastra, dan Pendidikan, 2026)
This study aims to analyze the representation of social and humanitarian values in the song “Heal the World” by Michael Jackson and to examine its relevance to social reality and Sustainable Development Goals (SDG 16: Peace, Justice, and Strong Institutions). This research employs a qualitative method based on the framework proposed by John W. Creswell, where the data consist of words, phrases, and sentences derived from the song lyrics. The data were collected through documentation and library research and analyzed through stages of data condensation, coding, theme identification, and interpretation. The findings reveal several major themes, namely peace as an ideal social condition, social criticism toward injustice and lack of empathy, humanitarian values as the foundation of social harmony, and individual responsibility in creating social change. The song reflects social realities such as conflict, inequality, and human suffering, while also functioning as a form of social criticism toward societal conditions. In conclusion, “Heal the World” serves as both a reflection of social conditions and a medium of social criticism that remains relevant in contemporary society and supports the values of SDG 16.